Understanding the Concept of Being in general: From Being and Time back to Young Heidegger - Filippopoulos, Yorgos G. (Conatus - Journal of Philosophy, 2024)
This paper exhibits a way of understanding Heidegger’s concept of being in general [Sein überhaupt] – the central aim of Being and Time’s questioning – by getting insight into his early years. I argue that the term “being” [Sein] as Heidegger understands it in the early 1920s describes the meaningful relation between humans and the things of their surrounding world which is given to us as a fact. I maintain that Sein überhaupt refers to this fact, i.e., the fact that every particular being is always with a certain meaning for us. I come to this conclusion by exploring (1) Heidegger’s early analysis of Umwelterlebnis, (2) his early description of medieval transcendentia, (3) his critique of formalization and the introduction of formal indication. Lastly, (4) I observe the way Heidegger introduces the concepts of Sein and Sein überhaupt pointing to the simple fact of beings’ being in meaningful relation to us.